THE GEOPOLITICAL IMPORTANCE OF YEMEN'S GEOGRAPHY IN IRANIAN STRATEGY - Ebtihal Nasser Jubeir; Omar Kamel Hassan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The study aims to know the geographical location of Yemen and its importance to Iran , through which Iran reflects its vision to find a foothold in the region , as the repercussions of Iranian domination on Yemen with its control over it become Gulf oil tankers in general and Saudi Arabia in particular within the circle of danger , as the presence of Iran has done everything it can to establish a presence in the Red Sea region , and if Ansar Allah takes power in Yemen, it could be a large-scale Iranian stronghold in the future